Calibration of mass and conventional mass of weights 2 kg, 1 kg, 200 g, 50 g, 1 g and 200 mg - Becerra, Luis Omar; Peña, Luis Manuel; Vargas, Boris Escalante; Almonte, Luz Cori; Martín Quiroga Rojas, Aldo; Bermúdez Coronel, lvaro; Soto, Jhon J Escobar; Naula, Wilson; Florencio, Arnaldo; Valenzuela, a Lourdes; Alfaro, Olman Ramos; Peña, Marcela Prenda; et al. (IOP Publishing, 2018)
This report describes the results of a supplementary comparison between SIM NMIs, which was carried out to evaluate the consistency of the measurements of calibration in high accuracy mass standards using the normalized error criteria (2 kg, 1 kg, 200 g, 50 g, 1 g and 200 mg). The supplementary comparison was carried out from April 2012 to July 2013. Main text To reach the main text of this paper, click on Final Report. Note that this text is that which appears in Appendix B of the BIPM key comparison database kcdb.bipm.org/. The final report has been peer-reviewed and approved for publication by the CCM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).